Antidepressants in breast milk: comparative analysis of excretion ratios - Schoretsanitēs, Geōrgios; Augustin, Marc; Saßmannshausen, Helena; Franz, Cordula; Gründer, Gerhard; Paulzen, Michael (Archives of women's mental health, 2018)
Despite increasing prescription rates of antidepressants in pregnant and breastfeeding women over the past decades, evidence of drug exposure for neonates through lactation is very sparse. Concentrations of three antidepressants citalopram, sertraline, and venlafaxine were measured in maternal blood and breast milk in 17 women receiving antidepressant therapy during breastfeeding period. We also computed concentration-by-dose-ratios (C/D) and milk to serum (plasma) penetration ratios (M/P). Non-parametric tests were applied. Serum concentration of citalopram and daily dosage correlated positively while daily dosage and mother milk concentration did not (rho = 0.939, p = 0.005, and rho = 0.772, p > 0.05 respectively). A significant correlation was also found between serum and milk concentrations (rho = 0.812, p = 0.05). Venlafaxine daily dosage correlated positively with the active moiety milk concentration (rho = 0.949, p = 0.014). No significant correlations were reported for sertraline. The amount of antidepressant concentrations to which neonates may be exposed, assessed as absolute infant dose (AID), was particularly low with the highest median AID being 0.16 mg/kg/day for venlafaxine. No significant difference was detected for the M/P ratios between different drugs (p > 0.05), whereas the comparison of C/D ratios revealed lower values in the sertraline group, with the highest values reported for citalopram group (p = 0.007 for serum concentrations and p = 0.008 for mother milk). Findings suggest that breastfeeding under antidepressant treatment constantly exposes children with measurable drug concentrations. As daily dosage and serum concentration of the antidepressants did not predict drug concentrations in mother milk, measuring of drug concentrations in milk helps to quantify drug exposure during breastfeeding. More data—even data of drug concentrations in breastfed children—are needed to better assess the effects of drug exposure on children’s development.
Published online: 16 August 2018
Gesehen am 27.04.2020